Development of the Paris definition of early Crohn's disease for disease-modification trials: results of an international expert opinion process. - Peyrin-Biroulet, L; Billioud, V; D'Haens, G; Panaccione, R; Feagan, B; Panés, J; Danese, S; Schreiber, S; Ogata, H; Hibi, T; Higgins, P; Beaugerie, L; et al. (2012)
We report the findings and outputs of an international expert opinion process to develop a definition of early Crohn's disease (CD) that could be used in future disease-modification trials. Nineteen experts on inflammatory bowel diseases held an international expert opinion meeting to discuss and agree on a definition for early CD to be used in disease-modification trials. The process included literature searches for the relevant basic-science and clinical evidence. A published preliminary definition of early CD was used as the basis for development of a proposed definition that was discussed at the expert opinion meeting. The participants then derived a final definition, based on best current knowledge, that it is hoped will be of practical use in disease-modification trials in CD.